Early larvae ontogeny of the Neotropical fishes: Prochilodus costatus and P. argenteus (Characiformes: Prochilodontidae) - dos Santos, José Enemir (2016)
Early development of fish larvae is a highly dynamic process and its study may provide important information about ontogenetic development, bioenergetic growth, behaviour, taxonomic characteristics for identification in natural environments, identification of spawning areas, and population monitoring. With the aim to provide knowledge about their growth and behaviour, to support larval rearing, and also taxonomic purposes, we studied the life history of the Prochilodus argenteus and P. costatus from hatching until the complete absorption of the yolk. Larvae were obtained through artificial reproduction at the Hydrobiology and Aquaculture Station of Três Marias, Minas Gerais, Brazil. Immediately after hatching, 100 larvae of each species were put in two plastic incubators for conditioning. On a daily basis, larvae behavior was recorded and 14 larvae of each species were collected to analyse body morphology. On the first day after hatching, larvae of P. costatus and P. argenteus showed an elongated and transparent body; the yolk sac was filled with individualized yolk globules. In both species, the embryonic fin rounded the caudal region of the body, the retina was non-pigmented and the gut was obliterated. At the second day post-hatching, larvae of both species dendritic chromatophores had emerged, the mouth was obliterated and the pectoral fin was observed. The larvae showed 38-43 myomeres in P. costatus and 42-43 in P. argenteus. For both species, the gas bladder was inflated and the lumen of the gut was already open. On the third day post-hatching, the mouth of P. costatus and P. argenteus was already open in a sub-terminal position; the retina was pigmented; the gill arches had lamellar protrusions and were partially covered by the operculum. On the fourth day post-hatching, the pigmentation pattern was maintained with greater intensity; the mouth occupied a terminal position, the yolk sac was almost completely reabsorbed, and the pectoral and caudal fins showed mesenchymal rays in both species. The gut showed a broad lumen with folded mucosa and epithelium with striated border. The larvae of both species showed similar swimming behaviour. Our study provided understanding about the morphophysiological aspects, species identification, larval development and growth, and the ontogenic characteristics of two Neotropical fishes with importance for commercial and sports fishing